Realistične teorije znanja - Klemenčič, Eva (Šolsko polje, 2012)
Today, much of the debate on the national school curriculum follows to some fundamental division which appeared in epistemological theories, splitting the realistic conception and antirealistic conception of knowledge. In this article, I have tried to show the similarities and differences of the various realisms. Realism is based on the idea that there is human cognition independent of reality to which human knowledge is faithfully (as appropriate) reflected. A culturally specific perspective, in watching the reality may not be relevant component of knowledge, which is in ideal conditions, culturally non-specific. In the field of education, this can become the idea of single or universal human knowledge argued in favor of at least partial global unification of curricula in those areas where the subject learning is not human culture itselves. The opposite is true for antirealistic theories of knowledge, which in the latter see especially specific products from each society and culture, with the system of concepts and ideas being the inevitable role of mediation between the learning subject and the cognitive object. After transferring to the field of education antirealistic, theories of knowledge become arguments in favour of the thesis that the curriculum content on a global level cannot possibly be uniform, as derived from the sociocultural systems of terms and concepts related to the specific perspective, which is a constitutive element of knowledge. However, in this article I have focused on the first part of the split, that being realism and realistic theories of knowledge.
Keywords: realism; vzgoja in izobraževanje; realistic theories of knowledge; realizem; Russell, Bertrand; znanje; knowledge; teorija znanja